Germanium nanoparticles film as a room-temperature electron transport layer for organic solar cells. (15th September 2021) - Li, Chang; Zhou, Zhukun; Liu, Ke; Sun, Xiaoxiang; Tao, Jiayou; Wang, Jifei; Zou, Zhijun; Liao, Gaohua; Li, Fen; Ni, Jian; Zhang, Jianjun
Graphical abstract: In this paper, we report the amorphous Ge NPs film which is fabricated at room-temperature by PECVD method. The uniform, compact and smooth film is formed by orderly packing of the Ge NPs in the longitudinal direction, resulting in the formation of columnar structures in the Ge NPs film. The electrical, optical properties and energy levels of the Ge NPs film meet the requirements of the OSCs for ETL, and the PTB7:PC70 BM OSCs with the Ge NPs ETL shows the PCE of 7.38%. Highlights: The amorphous Ge NPs film is fabricated by using the PECVD method at room temperature. The compact and orderly packing of the NPs in the longitudinal direction leads to the formation of columnar structures in the Ge NPs film. The electrical, optical properties and energy levels of the Ge NPs film meet the requirements of the OSCs for ETL. The PTB7:PC70 BM OSCs with the Ge NPs ETL shows the PCE of 7.38%. Abstract: The performances of the organic solar cells (OSCs) largely depends on the selection and preparation of the electron transport layer (ETL). In this paper, the uniform and compact Ge nanoparticles (NPs) film was fabricated by using the plasma enhanced chemical vapor deposition (PECVD) method at room temperature. The Ge NPs film is formed by close packing of amorphous Ge particles with an average diameter of 6.05 nm, and the film shows a fairly smooth surface with a root-mean-square (RMS) roughness of 0.6419 nm. The results shows that Ge NPs film exhibits n-type characteristics, and the longitudinal conductivity of the film is 1.90 × 10 −5 S/cm, which is better than that of the ZnO NPs film. The excellent longitudinal charge transport characteristics is attributed to the existence of the columnar structures in the Ge NPs. In addition, the Ge NPs film shows a visible light transmittance comparable to that of the ZnO NPs film. More importantly, the energy levels of the Ge NPs film meets the requirements of the PTB7:PC70 BM OSCs for the ETL, and the devices with the Ge NPs ETL shows the power conversion efficiency (PCE) of 7.38%. The characteristic of room temperature preparation make the Ge NPs ETL may become a reliable choice for the flexible devices in the near future.